Improved biomass cooking to fight climate change and poverty - Jörg Peters (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
Inefficient firewood and charcoal usage contributes massively to global greenhouse gas emissions and causes four million mortal diseases a year. - Relative to other climate protection measures, public investments in the dissemination of improved biomass cooking stoves provide a very effective low cost measure to reduce greenhouse gas emissions. More than three billion people in developing countries rely on inefficient cooking stoves fuelled by firewood and charcoal. Improved cookstoves have the potential to reduce greenhouse gas abatement costs to only 3 Euro per ton of CO2 equivalent and at the same time alleviate poverty.
Keywords: 330; Immissionsschutz; Treibhausgas-Emissionen; Herd; Bioenergie; Innovationsdiffusion; Entwicklungsländer